Village Fund Direct Cash Assistance Distribution: A Justice Analysis from an Islamic Economic Perspective (Cenrana District Case Study) - Nikmawati; Arifin Sahaka; Kamiruddin (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2026)
Purpose: This study aims to examine the fairness of the distribution of Village Fund Direct Cash Assistance (BLT) from an Islamic economic perspective in Cenrana District, Bone Regency, and to assess its alignment with the principles of distributive justice in Islamic economics. Design/methodology/approach: This research adopts a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation involving village officials and BLT recipients. The analysis focuses on evaluating targeting accuracy, transparency, and fairness in the distribution process based on Islamic economic principles. Findings: The results indicate that the distribution of BLT Village Fund has generally helped beneficiaries meet their basic needs. However, challenges remain, particularly in the accuracy of targeting and the transparency of the distribution process. From an Islamic economic perspective, the implementation is relatively aligned with the principles of justice, especially in prioritizing vulnerable groups, although improvements in equity and accountability are still required. Practical implications: These findings emphasize the need for strengthening transparency, improving data accuracy, and enhancing community involvement in the determination of beneficiaries to ensure a more equitable distribution of social assistance at the village level. Originality/value: This study contributes to the literature by integrating the analysis of BLT Village Fund distribution with the principles of Islamic economic justice, providing empirical insights into the implementation of faith-based distributive justice in local government social assistance programs